Tamoxifen Pioneering Medicine in Breast Cancer - Maximov, Philipp Y.; McDaniel, Russell E.; Jordan, V. Craig (Milestones in Drug Therapy, 2013)
Tamoxifen is a pioneering medicine for the treatment and prevention of breast cancer. It is the first drug targeted therapy in cancer to be successful. Tamoxifen targets the tumor estrogen receptor. The therapy is known to have saved the lives of millions of women over the past 40 years. This monograph, written by V. Craig Jordan - known as the "father of tamoxifen" - and his Tamoxifen Team at the Georgetown University Washington DC, illustrates the journey of this milestone in medicine. It includes a personal interview with V. Craig Jordan about his four decades of discovery in breast cancer research and treatment. V. Craig Jordan was there for the birth of tamoxifen as he is credited for reinventing a "failed morning after contraceptive" to become the "gold standard" for the treatment of breast cancer. He contributed to every aspect of tamoxifen application in therapeutics and all aspects of tamoxifen's pharmacology. He discovered the selective estrogen receptor modulators (SERMs) and explored the new biology of estrogen-induced apoptosis.